The Influence of Work Motivation and Workload on Employee Productivity - Yamang, Syahrul Mubarak; Zaharuddin, Zaharuddin; Supriyadi, Supriyadi (International Journal of Business, Law, and Education, 2025)
In the era of globalization, competition among companies and institutions has become increasingly intense. This study aims to examine the influence of work motivation on employee productivity, the influence of workload on employee productivity, and the simultaneous effect of work motivation and workload on employee productivity. The research employs a quantitative methodology with a survey approach. Data were collected through research instruments designed by the researchers, including instruments for work motivation, workload, and employee productivity. The results indicate that: (1) work motivation has a positive effect on employee productivity; (2) workload does not have a significant positive effect on employee productivity; (3) work motivation and workload, when considered simultaneously, have a positive effect on employee productivity.